2009
DOI: 10.4039/n09-022
|View full text |Cite
|
Sign up to set email alerts
|

Activity of flying beetles (Coleoptera) at two heights in canopy gaps and intact forests in a hardwood forest in Quebec

Abstract: Abstract-We studied the effects of forest height and forest gap on assemblages of flying beetles in an American beech (Fagus grandifolia Ehrh. (Fagaceae) -sugar maple (Acer saccharum Marsh. (Aceraceae)) forest in Quebec. From June until August of 2005, beetles were collected in Lindgren funnel traps placed in the canopy (20-25 m height) and upper understorey (3-5 m height) in proximity to five forest gaps (15-30 m in diameter) (at the edge of the forest opening or within the closed-canopy forest). We collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 19 publications
(22 reference statements)
1
24
0
6
Order By: Relevance
“…The highest abundance occurred in the elevated stratum in Hirao et al (2009) andHammond et al (2004), near the ground in Preisser et al (1998) and Manak (2007) or was comparable in Ulyshen and Hanula (2007). What is more, species richness peaked in the canopy for Schroeder et al (2009) and Kappes and Topp (2004), at low levels for Hammond et al (2004), Vodka et al (2009), Ulyshen and Hanula (2009) and Foit (2010) and was equivalent in the two strata for Ulyshen and Hanula (2007) and Hirao et al (2009). Notwithstanding forest type or insect group, no obvious trend could be inferred.…”
Section: Is the Bulk Of Saproxylic Beetle Diversity Mainly Supported mentioning
confidence: 62%
See 1 more Smart Citation
“…The highest abundance occurred in the elevated stratum in Hirao et al (2009) andHammond et al (2004), near the ground in Preisser et al (1998) and Manak (2007) or was comparable in Ulyshen and Hanula (2007). What is more, species richness peaked in the canopy for Schroeder et al (2009) and Kappes and Topp (2004), at low levels for Hammond et al (2004), Vodka et al (2009), Ulyshen and Hanula (2009) and Foit (2010) and was equivalent in the two strata for Ulyshen and Hanula (2007) and Hirao et al (2009). Notwithstanding forest type or insect group, no obvious trend could be inferred.…”
Section: Is the Bulk Of Saproxylic Beetle Diversity Mainly Supported mentioning
confidence: 62%
“…Nonetheless, contrasting responses were found in the literature for community divergence between canopy and forest floor (Table 4). A significant inter-strata dissimilarity was revealed for beetles (Ulyshen and Hanula, 2007), saproxylic beetles (Hammond et al, 2004;Schroeder et al, 2009;Foit, 2010), bugs (Goßner, 2009) and parasitic wasps (Pucci, 2008). However, Müller and Goßner (2010) demonstrated a low beta diversity of saproxylic beetles among vertical strata.…”
Section: Are Canopy Assemblages Only Nested Subsets Of Understory Assmentioning
confidence: 97%
“…Additionally, studies over a vertical gradient in the forest reveal patterns of species' distribution which would have gone unnoticed using the traditional, ground-based techniques [21,22]. Shubeck [23] was the first to compare the response of burying beetles between ground-level carrion Psyche and carrion suspended 1.5 m above the ground.…”
Section: Introductionmentioning
confidence: 99%
“…Using traps at several heights above the ground, Ulyshen and Hanula [25] showed that the vertical distribution of beetles, even within a family, can be diverse. Schroeder et al [22] recorded carrion beetles over 3-25 m, the greatest vertical gradient investigated so far. The evidence from these studies lend insight into which species can be caught in the canopy, but studies investigating why some beetles occur in the canopy have yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Arthropod diversity usually shows a clear stratification and decreases from the canopy to lower strata (Longino and Nadkarni, 1990;Basset et al, 1992Basset et al, , 2001Basset et al, , 2003Stork and Grimbacher, 2006;Schroeder et al, 2009;Davis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%